Revitalisation strategies of urban public space in George Town World Heritage site / Maimunah Ramlee … [et al.] - Ramlee, Maimunah; Omar, Dasimah; Mohd Yunus, Rozyah; Samadi, Zalina (Universiti Teknologi MARA Cawangan Selangor, 2019)
Revitalisation of urban public space in Core Zone, George Town World Heritage Site (GTWHS) is a mechanism to redevelop the public space area in accordance with the development growth and population. This paper has discussed the revitalisation factors in creating a great urban public space. The main objectives of this study are : 1) to identify urban public space characteristics which is significantly for revitalisation purposes, and 2) to derive the more functionally public space that fit the modern urban life. A combination of method was applied, including quantitative and qualitative method. It has been concluded that it is important to revitalise urban public space through planning and urban management.